Mediating Effect of Organizational Commitment Between Islamic Human Resource Practices and Organizational Performance Among Islamic Banks of Bangladesh - Bablu Kumar Dhar; Hatem Mohammed Rahouma; Farid A. Sobhani; Mir Mohammed Nurul Absar; Rosnia Masruki; Mahazan Abdul Mutalib @ Talib (Universiti Sains Islam Malaysia, 2024)
This paper aims at exploring the impact of Islamic human resource (HR) practices on organizational performance though organizational commitment. Data were collected from randomly selected 170 branch managers of six Islamic Banks listed on Dhaka Stock Exchange of Bangladesh. After collecting data, descriptive analysis and structural equation model were done to examine reliability and validity of the model. By analysis, the study finds that Islamic HR practices have more significant impact on organizational performance though organizational commitment rather than the direct effect of Islamic HR practices to organizational performance. The findings of the study advocate that Islamic banks should emphasize more on Islamic HR practices and organizational commitment to uphold their organizational performance.